Late Oligocene Tibetan Plateau Warming and Humidity: Evidence From a Sporopollen Record. (23rd January 2019) - Wu, Fuli; Miao, Yunfa; Meng, Qingquan; Fang, Xiaomin; Sun, Jimin
Abstract: Dramatic warming in the late Oligocene occurred after 8 Ma, characterized by ocean warming and a collapse of the Antarctic ice sheet (the late Oligocene warming event [LOWE]); however, few terrestrial records have yet been employed to verify the LOWE and investigate its associated driving forces. The Nima Basin, located in the central Tibetan Plateau contains thick Oligocene sediments, allowing its ecological record to be used as verification of the LOWE. Here we used the reconstructed vegetation record from the Nima Basin in the 1, 100‐m‐thick DZC section, aided with zircon U‐Pb dating of the interbedded tuffite layers. Two tuffite layers yielded ages of about 23.4 and 24.8 Ma; thus, the sedimentary age of the whole section is predicted to be 27.5–22.4 Ma. Sporopollen analysis revealed that the dominant taxa throughout the whole section were conifers (over 85%), including Piceapollis, Pinuspollenites, and Abietpollenites . One notable feature is that the broad‐leaved trees (e.g., Quercoidites and Meliaceoidites ) increased obviously (averaging from 0.9% to 6.6%, max 41.2%) after 25.6 Ma. This change could be interpreted as a response to late Oligocene global warming, which changed the forest line and corresponding plant species composition. The mean average precipitation of 400–850 and 800–1, 000 mm, respectively, inferred from the above vegetation types in the Nima Basin, both exceed the present 150 mm. This indicates that the south Asian monsoon had already developed in the Oligocene and that the LOW event accompanied the global warming. Key Points: The U‐Pb dating shows the DZC section; Nima Basin was deposited mainly in the late Oligocene The sporopollen results of the DZC section show conifers were dominant but angiosperms increased after 25.58 Ma The changed vegetation was a response to the LOWE and suggested the south Asian monsoon enhanced at that time